A Comprehensive Survey on the Non-Invasive Passive Side-Channel Analysis - Socha, Petr; Miškovský, Vojtěch; Novotný, Martin (Sensors (Basel, Switzerland), 2022)
Side-channel analysis has become a widely recognized threat to the security of cryptographic implementations. Different side-channel attacks, as well as countermeasures, have been proposed in the literature. Such attacks pose a severe threat to both hardware and software cryptographic implementations, especially in the IoT environment where the attacker may easily gain physical access to a device, leaving it vulnerable to tampering. In this paper, we provide a comprehensive survey regarding the non-invasive passive side-channel analysis. We describe both non-profiled and profiled attacks, related security metrics, countermeasures against such attacks, and leakage-assessment methodologies, as available in the literature of more than twenty years of research.
Keywords: zabezpečení počítačových systémů; Software; side-channel attacks; počítače; software; security; Computer Security; Computers; side-channel countermeasures; side-channel analysis; embedded systems